Impactos das práticas da acreditação no desempenho hospitalar: um survey em hospitais do estado de São Paulo - Alástico, Gabriel Pedro (2013)
The demand for improving the health care services from social actors (Government, Insurance Companies, Patients and Payers) has carried out the hospitals to implement actions of performance improvement. In Brazil, it occurs in a context of deficiency in the management and efficiency of the processes. This thesis analyzes the implamentation impact of NAO‟s Accreditation practices (the brazilian certification most required in the healt care services) on the hospital performance as well as the moderators factors (hospital ownership, hospital size, Accreditation level and Accreditation time) influence in this relationship. A survey research involving the 32 Accredited hospitals from Sao Paulo State was carried out during six months. The survey evaluated the managers‟ perception about the hospital performance improvement comparing the current hospital performance with the hospital performance before the adoption of Accreditation practices. A statistic analysis determined the statistical significance between the Accreditation practices and the hospital performance improvement. Moreover, the most critical Accreditation practices for improving the hospital performance were identified. Finally, managerial actions were proposed to improve the performance of hospitals clusters composed by hospitals with similar management characteristics. The statistical analysis results identified a significant influence of the Accreditation practices in operational efficiency under the action of size and Accreditation time of the hospitals. The critical practices to the hospital performance improvement are the risks management practices and the managerial inovation practices. The first improve the hospital infection rate and the latter improve the medication errors rate.